A comprehensive investigation on application of microsilica and rice straw ash in rigid pavement. (20th August 2020) - Pandey, Arunabh; Kumar, Brind
Highlights: Rice straw ash (RSA) particles are acicular and hydrophilic in nature. Up to 10% replacement of OPC by RSA and by microsilica (MS) is possible in mortar cubes. MS is more effective than RSA in improving the mechanical strengths of concrete. The admixing of MS and RSA significantly enhances the durability properties of concrete. The admixing of 10% RSA reduces the slab thickness of rigid pavement by 11%. Abstract: This study investigated the potential of rice straw ash (RSA) (produced from open-air burning of rice straw) and microsilica (MS) as a pozzolan in rigid pavements. Proportions of RSA (5%–30%), MS (2.5%–10%) and combination of RSA (5%, 10%) + MS (5%, 7.5%) by weight of OPC in the paste and mortar were studied. Various tests like normal consistency, setting time, soundness and X-ray diffraction (XRD) analysis were performed on the cementitious paste. It was observed that the admixing of MS did not affect the setting times and soundness of the cement paste but increased the normal consistency while admixing of RSA remarkably increased all of them. It was also found that OPC can be replaced by RSA up to 10% and by MS up to 7.5% in mortar without any loss of compressive strength. In the assessment of mechanical strengths of concrete, it was found that RSA and MS increase various strengths of concrete up to 7% and up to 24%, respectively. Furthermore, these results were validated by XRD and Scanning electron microscope (SEM) analysis. In the evaluation of durability properties of concrete, it was observed that MS and RSA significantly increase the defense mechanism of concrete to water absorption, chloride ion penetration, acid attack and accelerated carbonation curing (ACC). The design thickness of the concrete slab of the selective concrete mixes was computed as per structural design in accordance with IRC 58:2015. The cost comparison was made on the basis of the total cost of 1 m 3 of concrete and the total cost of constructing 1 km of 4 lane National Highway (NH) (one-way carriageway). The admixing of 10% RSA reduces the slab thickness by 11%, cost of 1 m 3 of concrete by 3% and cost of constructing NH by 14%.